Dilated Perivascular Space in the Midbrain May Reflect Dopamine Neuronal Degeneration in Parkinson’s Disease - Li, Yanxuan; Zhu, Zili; Chen, Jie; Zhang, Minming; Yang, Yunjun; Huang, Peiyu (Frontiers in Aging Neuroscience, 2020)
Background: The imbalance between the production and clearance of alpha-synuclein and its consequent accumulation plays a pivotal role in the pathogenesis of Parkinson’s disease (PD). The diminished clearance of alpha-synuclein may be partly attributable to impaired interstitial fluid, which can be reflected by the extent of dilated perivascular space (dPVS). We studied the association between dPVS and dopamine neuronal degeneration. Method: We screened 71 healthy controls (HCs) and 88 patients from the Parkinson Progression Markers Initiative database. The dPVS was evaluated in different brain regions on axial T2-weighted images, and dopamine transporter (DAT) imaging data was used to elucidate the extent of dopaminergic neuronal degeneration. Patients with PD were further divided into two groups (SN+PD and SN-PD groups) according to whether dPVS was observed in the substantia nigra (SN). DAT uptake values and clinical scales were compared between the patients with PD and HCs and against dPVS scores. We also investigated the correlation between baseline dPVS scores and longitudinal DAT changes. Results: Relative to the HCs, patients with PD had more dPVS in the SN and basal ganglia. PD patients with dPVS in the SN region exhibited a greater expression of tau protein in cerebrospinal fluid (P=0.038) and a trend towards decreased DAT binding (P=0.086) relative to those without SN dPVS. No correlations were found between dPVS scores and DAT uptake values or between dPVS scores and longitudinal DAT changes. Conclusion: The dPVS in the SN of patients with PD may reflect the degeneration of dopaminergic neurons.